2019
DOI: 10.1016/j.mcn.2019.103390
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta impairs insulin signaling by accelerating autophagy-lysosomal degradation of LRP-1 and IR-β in blood-brain barrier endothelial cells in vitro and in 3XTg-AD mice

Abstract: Aberrant insulin signaling constitutes an early change in Alzheimer's disease (AD). Insulin receptors (IR) and low-density lipoprotein receptor-related protein-1 (LRP-1) are expressed in brain capillary endothelial cells (BCEC) forming the blood-brain barrier (BBB). There, insulin may regulate the function of LRP-1 in Aβ clearance from the brain. Changes in IR-β and LRP-1 and insulin signaling at the BBB in AD are not well understood. Herein, we identified a reduction in cerebral and cerebrovascular IR-β level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 74 publications
(112 reference statements)
3
43
2
Order By: Relevance
“…aβ 1-42 serves a vital role in the pathogenesis of ad owing to its strong aggregative ability and neurotoxicity (2). autophagy can protect against ad by clearing aβ deposition and preserving neuronal function (7). Furthermore, autophagic activity increases when cells experience injury, nutritional deficiency, growth factor deficits or high energy demand (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aβ 1-42 serves a vital role in the pathogenesis of ad owing to its strong aggregative ability and neurotoxicity (2). autophagy can protect against ad by clearing aβ deposition and preserving neuronal function (7). Furthermore, autophagic activity increases when cells experience injury, nutritional deficiency, growth factor deficits or high energy demand (4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that autophagy may be involved in ad pathogenesis (6). in addition, autophagy serves an important role in clearing aβ aggregation and preserving neuronal function in ad (7). another recent study also indicated that aβ 1-42 can induce autophagic cell death and autophagic vacuoles (8).…”
Section: Introductionmentioning
confidence: 95%
“…Amyloid β oligomers act on brain capillary cells to suppress expression of both LRP1 and of P-glycoprotein (P-GP); LRP1 acts in the abluminal capillary membrane to extract amyloid β monomers/oligomers from the brain extracellular space, and P-G acts on the luminal side to expel them into the circulation [ 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Hence, they act in tandem to expel intact amyloid beta from the brain.…”
Section: A Comprehensive Antioxidant Strategy May Aid Prevention Omentioning
confidence: 99%
“…In particular, Aβ level in the brain depends on the continuous control of Aβ influx and efflux via receptors RAGE and LRP1 located at the BBB (Zlokovic et al, 2010 ). Intake of diets high in SFAs, cholesterol and carbohydrates increases levels of circulating Aβ, disturbs its peripheral clearance by the liver and impairs brain Aβ clearance and efflux by decreased LRP1 and increased RAGE protein expression or activity (Kim et al, 2016 ; Gali et al, 2019 ). In turn, BBB dysfunction triggers oxidative stress and neuroinflammation, which causes enhancement of the activity of β-secretase and γ-secretase promoting generation of a new portion of Aβ peptides (Cai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%